Maternal obesity during gestation impairs fatty acid oxidation and mitochondrial SIRT3 expression in rat offspring at weaning. - Sarah J Borengasser; Franchesca Lau; Ping Kang; Michael L Blackburn; Martin J J Ronis; Thomas M Badger; Kartik Shankar (PLoS ONE)
In utero exposure to maternal obesity increases the offspring's risk of obesity in later life. We have also previously reported that offspring of obese rat dams develop hepatic steatosis, mild hyperinsulinemia, and a lipogenic gene signature in the liver at postnatal day (PND)21. In the current study, we examined systemic and hepatic adaptations in male Sprague-Dawley offspring from lean and obese dams at PND21. Indirect calorimetry revealed decreases in energy expenditure (p<0.001) and increases in RER values (p<0.001), which were further exacerbated by high fat diet (45% kcals from fat) consumption indicating an impaired ability to utilize fatty acids in offspring of obese dams as analyzed by PRCF. Mitochondrial function is known to be associated with fatty acid oxidation (FAO) in the liver. Several markers of hepatic mitochondrial function were reduced in offspring of obese dams. These included SIRT3 mRNA (p = 0.012) and mitochondrial protein content (p = 0.002), electron transport chain complexes (II, III, and ATPase), and fasting PGC-1α mRNA expression (p<0.001). Moreover, hepatic LCAD, a SIRT3 target, was not only reduced 2-fold (p<0.001) but was also hyperacetylated in offspring of obese dams (p<0.005) suggesting decreased hepatic FAO. In conclusion, exposure to maternal obesity contributes to early perturbations in whole body and liver energy metabolism. Mitochondrial dysfunction may be an underlying event that reduces hepatic fatty acid oxidation and precedes the development of detrimental obesity associated co-morbidities such as insulin resistance and NAFLD.